Utilization of shell waste as an adsorbent to reduce Fe (Iron) Metal - Uji Wahyuni, Endang; Pramono, Budi; S, Syarifuddin (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: So far, clam and crab shells have only been used for handicrafts such as wall hangings, or for animal feed mixtures. Shellfish shell waste contains high calcium carbonate, which is 98%, which has the potential to be utilized. Based on the results of previous studies on clam shell powder, the results were quite good at absorbing heavy metals. This research exploits the potential of shellfish in another form, namely shell ash as an alternative adsorbent that is environmentally friendly, because shell ash consists of compounds namely 7.88% SiO2, 1.25% Al2O3, 0.03% Fe2O3, 66.70% CaO, and 22.28% MgO. Based on the chemical composition, the CaO content in the shell ash is quite high so that the shell ash has the potential as an adsorbent. Purpose: to determine the ability of clam shells as an Fe adsorbent. Method: This type of research is quasi-experimental in nature, which is a research method that uses a quantitative approach, carrying out three control activities, manipulating activities and observation. In this study the researchers treated water containing Fe using blood clam shells and green mussel shells, as adsorbents. Results: Based on these results it can be seen that there is a decrease in iron (Fe) content by using variations in the size of clam shell granules as an adsorbent. The smaller the size of the clam shell granules, the lower the iron (Fe) content in groundwater. The highest percentage of reduction in iron (Fe) content was in 0.8 mm shell granules with a reduction percentage of 89%. Based on the research results, the ability of hemp shells to reduce Fe levels was very good, from a Fe level of 3.656 mg/liter after being filtered with blood clam media it decreased to a level of 0.132 mg/liter. Almost seeding the gold standard (ferrolite) which can reduce up to 0.033 mg/liter. Meanwhile, green mussels can reduce up to 2.64 mg/l. Conclusion: the ability of blood clam shells to reduce Fe levels is very good, able to reduce 96.39% (effective), almost seeding the gold standard (Ferolite) which can reduce up to 99.10%. Meanwhile, green mussels were only able to reduce up to 27.79% (not effective).